The Role of Biological and Environmental Factors in Infant Pneumonia: Findings from the 2023 Indonesian Health Survey - Leka Lutpiatina; Ratih Dewi Dwiyanti; Aima Insana (Baiman Bauntung Batuah Center, 2026)
Pneumonia continues to be a leading cause of morbidity and mortality in infants, particularly in developing countries, making risk factor analysis crucial to support evidence-based prevention efforts. This study analyzed factors associated with pneumonia in 28,610 infants aged one year and under using data from the 2023 Indonesian Health Survey to provide a national overview of the distribution of cases and their determinants. This study used a cross-sectional design and analyzed demographic variables, health characteristics, and environmental factors using descriptive analysis, chi-square tests, and odds ratios. The study results showed a pneumonia prevalence of 0.9%, with an increased risk in low birth weight infants (OR 2.425; 95% CI: 1.688–3.483) and infants with a history of diarrhea (OR 2.051; 95% CI: 1.211–3.475), while breastfeeding reduced the risk of pneumonia (OR 0.590; 95% CI: 0.447–0.778). The data also showed greater susceptibility among male infants and those living in urban areas. These findings confirm that pneumonia in infants is influenced by a combination of biological, environmental, and behavioral factors, so public health interventions need to strengthen monitoring of at-risk infants, increase the coverage and quality of breastfeeding, prevent diarrhea, and control exposure to air pollution, especially in urban areas. These findings provide an empirical basis for developing more targeted and effective infant health policies.